2016
DOI: 10.4238/gmr.15028106
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between estrogen receptor 1 gene polymorphisms and postmenopausal osteoporosis of the spine in Chinese women

Abstract: ABSTRACT. The purpose of this study was to evaluate single nucleotide polymorphism (SNP) variants of the estrogen receptor 1 gene (ESR1) at rs2234693 and rs9340799, as well as to investigate the relationship between ESR gene polymorphisms and postmenopausal osteoporosis (OP) of the spine in Chinese women. We recruited 198 postmenopausal women with OP and 276 healthy women between May 2012 and September 2015 in Zhongshan Hospital. Dual energy x-ray absorptiometry was used to measure the bone mineral density (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Additionally, the importance of ERs on cortical and trabecular bone, and also in different bone cell types have been widely explored (42). Although the studied genetic polymorphism rs2234693 and rs9340799 in ESR1 and rs1256049 and rs4986938 were not associated with PAP in the present study, they were previously associated with many different bone conditions (28,43) and oral conditions (43)(44)(45). The genetic polymorphisms rs2234693 and rs9340799 in ESR1 have been largely studied.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Additionally, the importance of ERs on cortical and trabecular bone, and also in different bone cell types have been widely explored (42). Although the studied genetic polymorphism rs2234693 and rs9340799 in ESR1 and rs1256049 and rs4986938 were not associated with PAP in the present study, they were previously associated with many different bone conditions (28,43) and oral conditions (43)(44)(45). The genetic polymorphisms rs2234693 and rs9340799 in ESR1 have been largely studied.…”
Section: Discussionmentioning
confidence: 61%
“…The evidence linking these polymorphisms and its haplotype to bone mineral density (28,46). Also they were associated with postmenopausal osteoporosis (28,43). According to Rivadeneira et al (47), genetic polymorphisms in ESR2 alone and in interaction with ESR1 can also influence the risk of bone fracture in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that ESR1 contributes to optimal periosteal bone formation through osteoblast progenitors, and a lack of ESR1 in osteoblasts leads to compromised bone mass and strength in female mice . Furthermore, ESR1 polymorphisms have been linked to postmenopausal osteoporosis of the spine in Chinese women . In addition, ESR1 has been identified as a target of miRNAs in the pathogenesis of various diseases .…”
Section: Discussionmentioning
confidence: 99%
“…ESR1 and ESR2 genes encode estrogen receptors, involved in pathological processes including breast cancer, endometrial cancer, and osteoporosis [ 22 ]. ESR1 is expressed in osteoblasts and osteoclasts, and is associated with postmenopausal osteoporosis of the spine in women [ 22 , 23 ]. This gene could be employed as a selection method to identify individuals at increased risk of osteoporosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…ESR1 is expressed in osteoblasts and osteoclasts, and is associated with postmenopausal osteoporosis of the spine in women [ 22 , 23 ]. This gene could be employed as a selection method to identify individuals at increased risk of osteoporosis [ 23 ]. In a previous large population-based cohort study, variants in the ESR2 gene were associated with an increased risk of vertebral fracture in postmenopausal women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%